2014
DOI: 10.1039/c4fo00387j
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the effects of formulation type and compositional mixtures on the antioxidant and cytotoxic activities of dietary supplements based-on hepatoprotective plants

Abstract: Artichoke (A), borututu (B) and milk thistle (M) are included in several supplements to provide beneficial effects. Different formulations (infusions, pills and syrups), with different proportions of A, B and M (1 : 1 : 1, 2 : 1 : 1, 1 : 2: 1, 1 : 1 : 2) within each formulation, were assayed to optimize the desired benefits. The antioxidant activity, anti-hepatocellular carcinoma activity, hepatotoxicity and bioactive compound contents were evaluated. Syrups tended to be the formulation with highest antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In the present study, the hydroalcoholic extract of the fresh aerial parts of E. purpurea combination; furthermore, and apart from that the syrup presented the highest antioxidant potential, followed by infusion preparation and then pills, it was the infusion preparation that provided the most pronounced toxic effects on hepatocellular carcinoma cell lines (HepG2) [56]. It means that probably other interfering factors, such as excipients, can exert significant modulatory effects and, therefore, while in the infusion preparation the bioactive molecules are free and able to exert their biological activity, they can be linked with other chemical constituents in phytopharmacological preparations (such as syrup and pills).…”
Section: Antioxidant Activity Of Phytopharmacological Preparations Bamentioning
confidence: 61%
“…In the present study, the hydroalcoholic extract of the fresh aerial parts of E. purpurea combination; furthermore, and apart from that the syrup presented the highest antioxidant potential, followed by infusion preparation and then pills, it was the infusion preparation that provided the most pronounced toxic effects on hepatocellular carcinoma cell lines (HepG2) [56]. It means that probably other interfering factors, such as excipients, can exert significant modulatory effects and, therefore, while in the infusion preparation the bioactive molecules are free and able to exert their biological activity, they can be linked with other chemical constituents in phytopharmacological preparations (such as syrup and pills).…”
Section: Antioxidant Activity Of Phytopharmacological Preparations Bamentioning
confidence: 61%
“…But the administration of the greater dosage (1g/kg) led to a potentially dangerous level of MDA [195,196]. In fact, current research has shown that the administration of large doses of antioxidants does not always have a positive impact, which could result in genotoxic effects [197,198].…”
Section: Artichoke (Cynara Scolymus)mentioning
confidence: 99%
“…Thus, bioflavonoids increase the supply of vitamin C to the body. The total amount of P-active compounds in Schisandra fruits is 100 mg/100 g [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidation of catechins is especially intense in the presence of oxidative enzymes, which explains the rapid browning of freshly squeezed juice. They contain from 50 to 150 mg/100 g [13,14].…”
Section: Introductionmentioning
confidence: 99%